Hsa_circ_0011385 accelerates the progression of thyroid cancer by targeting miR-361-3p - Xia, Fada (Cancer Cell Int, 2020)
BACKGROUND: Thyroid cancer is an endocrine malignancy that is growing in incidence worldwide. Despite progress in diagnostics and treatment of thyroid cancer, prognosis remains poor. Emerging research has shown that circular RNAs (circRNAs) have crucial regulatory roles in cancers. However, the possible functions and mechanisms of hsa_circ_0011385 remain undetermined. MATERIALS AND METHODS: Expression levels of hsa_circ_0011385 and miR-361-3p were evaluated by qRT-PCR assay. The interaction between hsa_circ_0011385 and miR-361-3p was verified by dual-luciferase reporter assay. Effects of hsa_circ_0011385 or miR-361-3p on cell viability, proliferation, cell cycle, apoptosis, migration and invasion were confirmed by cell counting kit-8 (CCK-8), carboxyfluoresceinsuccinimidyl ester (CFSE), flow cytometry, and Transwell assays in vitro. The effect of hsa_circ_0011385 on thyroid cancer progression was also determined by in vivo tumor formation assay. Target genes of miR-361-3p were predicted by gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, and the expression of apoptosis- and metastasis-related proteins were assessed by Western blot assay. RESULTS: Hsa_circ_0011385 upregulated in thyroid cancer; hsa_circ_0011385 knockdown inhibited thyroid cancer cell proliferation, migration and invasion, and promoted cell cycle arrest and apoptosis. In addition, hsa_circ_0011385 could negatively regulate miR-361-3p by functioning as a sponge. Hsa_circ_0011385 promoted thyroid cancer cell proliferation, migration and invasion and suppressed cell cycle arrest and apoptosis by targeting miR-361-3p in vitro. We also found that hsa_circ_0011385 knockdown dramatically inhibited thyroid cancer growth in vivo. Furthermore, hsa_circ_0011385 regulated expression of apoptosis and metastasis-related proteins in thyroid cancer. CONCLUSIONS: Hsa_circ_0011385facilitated thyroid cancer cell proliferation, invasion and migration, and inhibited thyroid cancer cell cycle arrest and apoptosis by targeting miR-361-3p, suggesting that the hsa_circ_0011385/miR-361-3p axis might be a promising therapeutic target for thyroid cancer.